Tetrahydrobenzimidazole TMQ0153 targets OPA1 and restores drug sensitivity in AML via ROS-induced mitochondrial metabolic reprogramming - Su Jung Park; Claudia Cerella; Jin Mo Kang; Jinyoung Byun; David Kum; Barbora Orlikova-Boyer; Anne Lorant; Michael Schnekenburger; Ali Al-Mourabit; Christo Christov; Juyong Lee; Byung Woo Han; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Acute myeloid leukemia (AML) is a highly aggressive cancer with a 5-year survival rate of less than 35%. It is characterized by significant drug resistance and abnormal energy metabolism. Mitochondrial dynamics and metabolism are crucial for AML cell survival. Mitochondrial fusion protein optic atrophy (OPA)1 is upregulated in AML patients with adverse mutations and correlates with poor prognosis. Method This study investigated targeting OPA1 with TMQ0153, a tetrahydrobenzimidazole derivative, to disrupt mitochondrial metabolism and dynamics as a novel therapeutic approach to overcome treatment resistance. Effects of TMQ0153 treatment on OPA1 and mitofusin (MFN)2 protein levels, mitochondrial morphology, and function in AML cells. In this study, we examined reactive oxygen species (ROS) production, oxidative phosphorylation (OXPHOS) inhibition, mitochondrial membrane potential (MMP) depolarization, and apoptosis. Additionally, metabolic profiling was conducted to analyze changes in metabolic pathways. Results TMQ0153 treatment significantly reduced OPA1 and mitofusin (MFN)2 protein levels and disrupted the mitochondrial morphology and function in AML cells. This increases ROS production and inhibits OXPHOS, MMP depolarization, and caspase-dependent apoptosis. Metabolic reprogramming was observed, shifting from mitochondrial respiration to glycolysis and impaired respiratory chain activity. Profiling revealed reduced overall metabolism along with changes in the glutathione (GSH)/oxidized glutathione (GSSG) and NAD⁺/NADH redox ratios. TMQ0153 treatment reduces tumor volume and weight in MV4-11 xenografts in vivo. Combination therapies with TMQ0153 and other AML drugs significantly reduced the leukemic burden and prolonged survival in NOD scid gamma (NSG) mice xenografted with U937-luc and MOLM-14-luc cells. Conclusion TMQ0153 targets mitochondrial dynamics by inhibiting OPA1, inducing metabolic reprogramming, and triggering apoptosis in AML cells. It enhances the efficacy of existing AML therapies and provides a promising combination treatment approach that exploits mitochondrial vulnerability and metabolic reprogramming to improve treatment outcomes in AML. Graphical Abstract